Laparoscopic vs open partial nephrectomy for T1 renal tumours: evaluation of long‐term oncological and functional outcomes in 340 patients. (6th June 2012) - Springer, Christopher; Hoda, M. Raschid; Fajkovic, Harun; Pini, Giovannalberto; Mohammed, Nasreldin; Fornara, Paolo; Greco, Francesco
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Whereas open nephron‐sparing surgery (NSS) represents the 'gold standard' in the surgical therapy of T1 renal tumours, with the advances in laparoscopic surgery, the refinement of intracorporeal suturing and the availability of haemosealant substances, the laparoscopic approach to NSS is increasingly used. Laparoscopic partial nephrectomy (LPN), however, is currently performed in just a few high‐volume reference centres, and its diffusion has been limited by the steep learning curve. Conversely, robot‐assisted LPN is emerging as a promising procedure, able to tackle the technical difficulties of LPN and leading to a broader diffusion of minimally invasive treatment of small renal masses. Our study provides long‐term follow‐up outcomes concerning surgical and oncological outcomes and a detailed evaluation of the renal function in patients affected by T1 renal cancers who underwent LPN and OPN. We showed that LPN could be safely performed in the therapy of T1 renal cancer, without impairing renal function. Objective To evaluate the long‐term oncological and functional outcomes of laparoscopic partial nephrectomy (LPN) compared with open partial nephrectomy (OPN) for pT1 renal tumours. Patients and Methods In this retrospective single‐centre study, 340 consecutive patients underwent LPN and OPN for localized, incidentally discovered, renal masses of <7 cm (cT1). The patients were matched for age, sex, body mass index, American Society of Anesthesiology score, tumour side (right or left kidney) and tumour characteristics (RENAL nephrometry score). Demographic data, peri‐ and postoperative variables, including operating time, estimated blood loss, complications, hospital stay, renal function, histological tumour staging and grading, and metastasis rates were collected and analysed. Results The median (sem) operating time for LPN and OPN was 145.3 (45.4) min and 155.2 (35.6) min, respectively (P = 0.07). The median (sem) warm ischaemia time was 11.7 (2.2) min in the LPN and 14.4 (1.9) min in the OPN group (P = 0.03). The median (sem) RENAL nephrometry scores for LPN and OPN were 5.9 (1.6) and 6.1 (0.3), respectively (P = 0.11). During follow‐up, the biochemical markers of glomerular filtration were completely normalized, showing the absence of renal injury and there was no significant difference in glomerular filtration rate between the groups, with median (sem) rates of 79.8 (3.0) mL/min/1.72m2 for the LPN and 80.2 (2.7) mL/min/1.72m2 for the OPN group at 5‐year follow‐up. The 5‐year overall survival and cancer‐specific survival rates, calculated using the Kaplan–Meier method, were 94% and 91% in the LPN group, and 92% and 88% in the OPN group. Conclusion LPN and OPN provide similar long‐term oncological outcomes in the therapy of T1 renal cancer. With regard to renal function, no damage to the kidney was found after LPN and OPN, with a complete normalization of renal function at the 5‐year follow‐up in both groups.